Substitution Of Commercial Feed and Local Feed For Quail Production (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
This study was conducted to determine the effect of substitution of commercial feed with local feed on the performance of quail (Coturnix-coturnix japonica) production. This research was conducted at the Field Laboratory of Animal Production Science and Technology, Faculty of Animal Husbandry, University using 64 quails in the grower phase (unsex), using commercial feed BP11 and local feed (milled corn and dried tofu dregs). The variables measured were feed consumption, body weight gain and feed conversion. The research design used a completely randomized design with 4 treatments and 4 replications. The data obtained included feed consumption, body weight gain and conversion were analyzed by analysis of variance. The results showed that substitution treatment of BP 11 commercial feed with local corn and tofu dregs up to 19% had no effect (P>0.05) on feed consumption, PBB and quail feed conversion.